Flow diverter implantation for CTA-negative giant vertebral artery dissection aneurysm: a case report - Li, Jun-Ting; Liu, Jian-Min; Zhao, Kai-Jun (Frontiers in Radiology, 2025)
ObjectiveTo evaluate the efficacy of flow diverter implantation for treating CTA-negative giant vertebral artery dissection aneurysm (VADA) and to address the challenges in lesion characterization using MRI.MethodsA 66-year-old male patient presented with a 3-month history of left facial numbness and dysarthria. Initial MRI-T1 revealed a mixed signal intensity lesion in the CPA region. However, both CTA and digital subtraction angiography (DSA) failed to identify any significant vascular abnormalities. Subsequently, CT-perfusion and dynamic contrast-enhanced computed tomography (DCE-CT) were performed to further characterize the lesion.ResultsDCE-CT revealed a giant VADA, which was significantly larger than the lesion initially detected by MRI and was identified as the cause of hypoperfusion in the posterior circulation. Based on these findings, a flow diverter implantation procedure was performed successfully without complications. Angiographic follow-up at 8 months demonstrated no recurrence of the lesion. At the 14-month clinical follow-up, the patient exhibited complete resolution of symptoms, with a mRS score of 0, indicating an excellent functional outcome.ConclusionFlow diverter implantation may be an effective treatment for CTA-negative giant VADAs. The limitations of MRI in accurately characterizing lesion size underscore the necessity of advanced imaging techniques, such as DCE-CT, for precise device selection and deployment.